Fatty acid profile of buffalo milk produced in southern Brazil - Godinho, Fernanda Marques de Souza; Friedrich, Maria Tereza; Modesto, Elisa Cristina; Mota, Amanda de Souza da (Acta Scientiarum. Animal Sciences, 2023)
Considering that buffalo milk is one of the richest in composition, mainly due to its fat fraction, the objective of this research communication was to determine the detailed fatty acid (FA) profile of buffalo milk produced in southern Brazil. Samples were collected from three farms that represent 100% raw buffalo milk producers of dairy products. Properties A and C had only one milking during the lactation period, and farm B had two milking. Farms A and B provided pasture and grain supplements, and farm C, provided only green pasture to the animals. A total of nine FA was identified: six saturated, two monounsaturated, and one polyunsaturated (conjugated linoleic acid - CLA). This study is the first to report the FA profile, including desirable fatty acids (DFA) like monounsaturated, polyunsaturated fatty acids, and stearic acid in buffalo milk from southern Brazil. The farms tested used different food management practices, as well as pasture management, showing that green pasture increases the fatty acid profile in buffalo milk. In addition, buffalo milk represented a good source of DFA for humans and opens a new field for the dairy industry that can explore the control of its FA composition, mainly through feed management.